Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1128/iai.67.4.1922-1928.1999
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to Yersinia Outer Proteins and Other Yersinia pestis Antigens after Experimental Plague Infection in Mice

Abstract: There is limited information concerning the nature and extent of the immune response to the virulence determinants ofYersinia pestis during the course of plague infection. In this study, we evaluated the humoral immune response of mice that survived lethal Y. pestis aerosol challenge after antibiotic treatment. Such a model may replicate the clinical situation in humans and indicate which virulence determinants are expressed in vivo. Immunoglobulin G enzyme-linked immunosorbent assay and immunoblotting were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 52 publications
1
39
0
Order By: Relevance
“…In addition to V-and F1-antigens, a range of virulence factors has been surveyed for their protective potential ( Table 1). Of these, only Yersinia secretory factor F (YscF), which forms the stem of the injectisome [60], and some of the Yops, offer any positive effect as immunogens, in terms of a delayed time to death or a significant increase in the lethal dose, 50% (LD50) value in immunized mice [61][62][63][64][65]. Despite the clear role of Pla as a surface protease and essential virulence factor in Y. pestis, immunization with a DNA construct expressing PLA in vivo did not induce protection in BALB/c mice [66].…”
Section: Virulence Factors As Immunogensmentioning
confidence: 99%
“…In addition to V-and F1-antigens, a range of virulence factors has been surveyed for their protective potential ( Table 1). Of these, only Yersinia secretory factor F (YscF), which forms the stem of the injectisome [60], and some of the Yops, offer any positive effect as immunogens, in terms of a delayed time to death or a significant increase in the lethal dose, 50% (LD50) value in immunized mice [61][62][63][64][65]. Despite the clear role of Pla as a surface protease and essential virulence factor in Y. pestis, immunization with a DNA construct expressing PLA in vivo did not induce protection in BALB/c mice [66].…”
Section: Virulence Factors As Immunogensmentioning
confidence: 99%
“…Previous report has shown that NO inhibited Fur repressor activity in vivo and Fur DNAbinding activity in vitro, while Fur-mediated iron acquisition system is an important mechanism of bacterial survival in the host [32]. It has been described that Y. pestis LcrV can influence the production of cytokines TNF-α and interferon-γ (IFN-γ) [33]. In the lungs, lcrV was up-regulated 844-fold, TNF-α 3.4-fold, while IFN-γ was down-regulated 2.2-fold at the 48 th hour after infection, implying that the production of these cytokines is a complex regulation procedure that will not determined by only one factor.…”
Section: Up-regulation Of Defense-related Genes Helps Host Against Ymentioning
confidence: 99%
“…However, a safe and effective pneumonic plague vaccine for human is not yet available in the United States [6,7]. Current vaccine development strategies focus on a few Y. pestis antigens [7], two major candidates being the outer capsule protein (F1) and the low calcium response protein V (LcrV), which induce good protective immune response against challenge with the pathogen [8,9]. While vaccines based on F1 alone fail to protect against F1 − virulent strains [10], LcrV based sub-unit vaccines confer protection against both F1 + and F1 − Y. pestis strains [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%